Pengaruh Metode Part And Whole Terhadap Hasil Belajar Lompat Jauh Gaya Jongkok Siswa Kelas VII SMP Negeri 1 Pampang - Julianto, Yopi; Kristin, Putri Cicilia; Mahendra, Agung (Indonesian Research Journal on Education, 2022)
This study aims to determine the effect of the part and whole method on the long jump learningoutcomes of class VII students at the State 1 Pampangan junior high school. The method used in this research is the experimental method. From the results of hypothesis testing on increasingpretest and posttest data, it is known that the hypothesis test results that there is a significant effect of the parth and whole method on the long jump learning outcomes of students of SMP Negeri 1 Pampangan t_count > t_table (2,341 > 1.70). These results indicate that the part and whole method applied in this study provides benefits or increases in the long jump learning outcomes of junior high school students of Pampangan 1 State.